Virtual reconstruction of the Neanderthal Amud 1 cranium. Issue 2 (7th August 2015) - Amano, Hideki; Kikuchi, Takeo; Morita, Yusuke; Kondo, Osamu; Suzuki, Hiromasa; Ponce de León, Marcia S.; Zollikofer, Christoph P.E.; Bastir, Markus; Stringer, Chris; Ogihara, Naomichi
ABSTRACT Objectives We describe a new computer reconstruction to obtain complete anatomical information of the ecto‐ and endocranium from the imperfectly preserved skull of the Neanderthal Amud 1. Materials and Methods Data were obtained from computed tomography scans of the fossil cranium. Adhesive and plaster were then virtually removed from the original specimen, and the fragments comprising the fossil cranium were separated. These fragments were then mathematically reassembled based on the smoothness of the joints. Both sides of the cranium were reassembled separately, and then aligned based on bilateral symmetry and the distance between the mandibular fossae obtained from the associated mandible. The position of the isolated maxilla was determined based on the position of the mandible that was anatomically articulated to the mandibular fossae. To restore missing basicranial and damaged endocranial regions, the cranium of Forbes' Quarry 1 was warped onto that of La Chapelle‐aux‐Saints 1, and the resulting composite Neanderthal cranium was then warped onto the reconstructed Amud 1 by an iterative thin‐plate spline deformation. Results Comparison of the computer reconstruction with the original indicated that the newly reconstructed Amud 1 cranium was slightly shorter and wider in the anteroposterior and mediolateral directions, respectively, suggesting that it was relatively more brachycephalic. The endocranial volume was estimated to be 1, 736 cm3, which was quite similar to the original estimated value of 1, 740 cm3. Discussion This new computer reconstruction enables not only measurement of new cranial metrics, but also inclusion of the Amud 1 specimen in three‐dimensional geometric morphometric analyses that were previously difficult due to its incompleteness. Am J Phys Anthropol 158:185–197, 2015. © 2015 Wiley Periodicals, Inc.